Fonologi Bahasa Arab Ibnu Sina dan Relevansinya dalam Pembelajaran Bahasa Arab di Madrasah Ibtidaiyah - Fitriyani; Aulia, Friska; Cahyani, Annisa Nur; Hanafi, Bardan; Susiawati, Iis (FKDP (Forum Komunikasi Dosen Peneliti), 2025)
This study examines Arabic phonology according to Ibn Sina and its relevance to learning in Madrasah Ibtidaiyah (Islamic elementary schools). The aim is to understand Ibn Sina’s concept of phonology and its application in teaching Arabic at the elementary level. The method used is library research by reviewing classical and modern sources related to makh?rij al-?ur?f (articulation points of letters) and ?if?t al-?ur?f (characteristics of letters). The results show that Ibn Sina views phonology as a science encompassing the physical, physiological, psychological, and semantic aspects of speech sounds. His scientific and systematic approach is relevant for improving pronunciation, listening, and understanding of sound meanings. Applying this theory in Madrasah Ibtidaiyah can help students develop auditory sensitivity, articulation accuracy, and fluency in speaking Arabic.